Mechanisms and Therapeutic Applications of RNA Delivery by Small Extracellular Vesicles - Reshke, Ryan (Université d'Ottawa / University of Ottawa, 2023)
MicroRNAs (miRNAs) are short non-coding RNA molecules that function in a ribonucleoprotein complex to silence gene expression through inhibition of translation and messenger RNA (mRNA) decay of complementary mRNAs. Short interfering RNAs (siRNAs) harness the same silencing machinery to enzymatically cleave complementary mRNAs leading to highly selective and potent reduction of gene expression. siRNAs represent a new class of therapeutics that have been approved for use against multiple disease-associated genes in the liver. Unfortunately, widespread use of siRNA therapeutics for the treatment of disorders in organs other than the liver has been hindered by difficulties delivering siRNAs into the cytoplasm of target cells. While existing delivery technologies have enabled reliable delivery in the liver, novel approaches are needed to unlock the full potential of siRNA therapeutics. Small extracellular vesicles (sEVs) are released from most cell types and travel through the body to deliver their contents, including microRNAs (miRNAs) into recipient cells. It has been suggested that they have evolved to be highly efficient at cargo delivery into a diverse population of tissues and cell types, making them an attractive option for delivery of siRNA therapeutics if they can be effectively packaged. This thesis is comprised of three manuscripts focusing on a novel mechanism for loading siRNAs into sEVs for therapeutic use. The first manuscript (Reshke, Taylor, Savard et al. 2020) describes our discovery that an RNA structure can be applied to package siRNAs into sEVs for efficient delivery into target cells. Specifically, we show that pre-miR-451, which has a uniquely short pre-miRNA hairpin is highly enriched in sEVs in almost all cell types. Importantly, changing the sequence of the short pre-miR-451 hairpin to include siRNA sequences causes those sequences to be packaged into sEVs as well, confirming that the packaging is dependent on the pre-miR-451 hairpin structure. We produce cell lines stably expressing siRNAs in the pre-miR-451 hairpin structure that release sEVs loaded with up to 30 copies of siRNA and use them to reduce target mRNA expression in vitro and in mice. We confirm that sEVs loaded with siRNA using the pre-miR-451 hairpin can deliver their siRNA cargo into cells of multiple organs beyond the liver including the kidney and small intestine, and do so more efficiently than synthetic lipid nanoparticles (LNPs) or sEVs loaded using other leading technologies like electroporation. The second manuscript (Dutta, Reshke et al. Submitted 2022) explores the feasibility of using these siRNA-loaded sEVs as therapeutics. We show that tangential flow filtration (TFF) is an ideal method for sEV production as it increases yield over 10-fold versus ultracentrifugation, and generates an sEV product that shows no signs of immunogenicity or toxicity in cultured human blood or in mice. We demonstrate the clinical relevance of sEVs in three distinct mouse models of chronic kidney disease (CKD), showing that siRNA can be delivered into kidney glomeruli knocking down disease-associated TRPC6 and APOL1 leading to improved kidney function and pathology. Finally, we show that sEV treatment can be scaled to reduce targets in larger animal models like rabbits. In the third manuscript (Reshke et al. in preparation 2023) we explore the mechanism that facilitates the active sorting of pre-miR-451 and other sequences in the pre-miR-451 hairpin structure into sEVs. We determine that the protein Midkine (MDK) is involved in this process and our data supports a model in which it shuttles pre-miR-451 into sEVs by physically binding to pre-miR-451 hairpins through a previously unknown RNA binding ability. Together, data presented here demonstrates that novel RNA binding proteins (RBPs) can play important biological roles outside of their known functions. One of these functions, the sorting of pre-miR-451 hairpins into sEVs by MDK, can be repurposed to effectively load siRNA into sEVs, generating a highly potent potential therapeutic that will hopefully unlock the capability of siRNA to treat a wide range of diseases in human patients.
Keywords: Extracellular vesicles; RNA therapeutics; MicroRNA